Evaluation of the inland fisheries in Basrah Province during 2020-2021, Iraq - Abdul-Razak Mohamed; Abdullah N. Abood (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The purpose of the study was to provide up-to-date information on inland fisheries landings in Basrah province, Iraq. During 2020-2021, the species composition, species and total landings, and trends at six landing locations in the research region were assessed. There were seven species of cyprinids, three species of cichlids, three species of mullet, and two species of sparids and silurids. The foreign species C. carpio, tilapias species, and C. auratus dominated landings, accounting for 44.2% of the entire catch. In contrast, the highly prized native species (M. sharpeyi, L. xanthopterus, C. luteus, and A. grypus) accounted for just 12.4%. In 2020 and 2021, the total landings reached 2,427.78 t and 2,365.15 t, respectively, greater than the previous years since 2009. This is attributable to the frequency of alien species and the rise in fishing effort, as measured by the number of fishermen and fishing vessels. Improving inland fisheries requires enhancing the stocks of native species, minimizing the dissemination and impacts of some exotic species, and activating national regulations governing fishing, exploitation, and conservation of aquatic life from the fisheries management perspective.